(untitled) - El Mustapha El anouar; Mohamed Jallal El adnani; Marouane Zouine; Mustapha El azzabi (Acta Informatica Pragensia)
Background: Recently, e-learning has emerged as a prominent tool for professional development in the education sector.Objective: The aim of this study was to examine teachers' perceptions of improving their professional skills through e-learning in the Béni Mellal-Khénifra region of Morocco.Methods: The research utilized a questionnaire survey method to collect primary data from 518 teachers. The variables in the proposed model were assessed using a self-tailored five-point Likert scale. Data analysis was performed through confirmatory factor analysis and structural equation modelling using analysis of moment structures (AMOS).Results: The results indicate the impact of teachers' satisfaction with their use of e-learning on the development of their professional competencies, without any direct effect of the actual use of e-learning on these skills. This suggests that satisfaction plays a mediating role between actual use and the development of teachers' professional competencies. The study also found that overall quality significantly affects both user satisfaction and actual use by teachers within an online learning context.Conclusion: As a practical implication, stakeholders should focus on the technical, semantic and efficient features of e-learning to maximize the opportunity for better results among teachers in terms of developing both technical and non-technical skills.